2015
DOI: 10.1016/j.physletb.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive calculation of complex Regge trajectories for the lightest f2 resonances and the K(

Abstract: We apply a recently developed dispersive formalism to calculate the Regge trajectories of the f2(1270) and f ′ 2 (1525) mesons. Trajectories are calculated, not fitted to a family of resonances. Assuming that these spin-2 resonances can be treated in the elastic approximation the only input are the pole position and residue of the resonances. In both cases, the predicted Regge trajectories are almost real and linear, with slopes in agreement with the universal value of order 1 GeV −2 . I. INTRODUCTIONThere is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Let us remark that in [2] it was shown that considering three subtractions lead to almost indistinguishable results. Therefore linear trajectories are not imposed a priori and, actually, a non-linear behavior was found for the f 0 (500) resonance [1].…”
Section: Dispersive Calculation Of Regge Trajectoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Let us remark that in [2] it was shown that considering three subtractions lead to almost indistinguishable results. Therefore linear trajectories are not imposed a priori and, actually, a non-linear behavior was found for the f 0 (500) resonance [1].…”
Section: Dispersive Calculation Of Regge Trajectoriesmentioning
confidence: 99%
“…Following [1,2], let us briefly recall the notation and the derivation of the dispersion relations that determine the Regge trajectory and residue of an elastic resonance just from its pole parameters. The partial wave expansion of the kaonpion scattering amplitude T (s, t) is…”
Section: Dispersive Calculation Of Regge Trajectoriesmentioning
confidence: 99%
See 3 more Smart Citations